2021
DOI: 10.1016/j.ijid.2020.11.190
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and genetic diversity of SARS-CoV-2 in Africa using whole genome sequences

Abstract: Highlights We established the introduction of diverse sub-Lineages of Lineage B into Africa within the first few months of the SARSCoV-2 outbreak. The evolutionary rate of SARSCoV-2 sequences in Africa is consistent with previous reports indicating congruence with global viral evolution. The G614 spike protein mutant was the most prevalent in this study.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 33 publications
1
35
1
1
Order By: Relevance
“…Our study presents that the highest substitution rate of the ORF10 protein appeared in Europe, followed by Africa ( Figure 2 B). Previous studies have reported the import of SARS-CoV-2 from Europe to Africa [ 47 , 48 ], which explains some similar patterns between Europe and Africa. To support surveillance, a paucity of SARS-CoV-2 sequence data from Africa requires further sequencing efforts on the African continent [ 47 ].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Our study presents that the highest substitution rate of the ORF10 protein appeared in Europe, followed by Africa ( Figure 2 B). Previous studies have reported the import of SARS-CoV-2 from Europe to Africa [ 47 , 48 ], which explains some similar patterns between Europe and Africa. To support surveillance, a paucity of SARS-CoV-2 sequence data from Africa requires further sequencing efforts on the African continent [ 47 ].…”
Section: Discussionmentioning
confidence: 60%
“…Previous studies have reported the import of SARS-CoV-2 from Europe to Africa [ 47 , 48 ], which explains some similar patterns between Europe and Africa. To support surveillance, a paucity of SARS-CoV-2 sequence data from Africa requires further sequencing efforts on the African continent [ 47 ]. Additionally, other viral proteins are also known to interact with many host proteins that participate in multiple biological processes such as protein trafficking, translation, and transcription [ 49 ].…”
Section: Discussionmentioning
confidence: 60%
“…Phylogenetic analysis showed that these viruses diversified during the duration of the pandemic into two major lineages, A and B, with several sublineage diversifications ( 4 ). A recent study indicated that the African SARS-CoV-2 sequences also diversified into two lineages, A and B, with B being more diverse with multiple sublineages ( 5 ). Here, we report the coding-complete genome sequence of a SARS-CoV-2 strain obtained from a sample taken on 5 March 2020 in Cameroon from a 58-year-old French patient who arrived from France on 24 February 2020.…”
Section: Announcementmentioning
confidence: 99%
“…Third, similar to other RNA viruses, SARS-CoV-2 has been shown to have a high mutational rate. Emerging data report world-wide evolutionary changes of the SARS-CoV-2 virus [ [7] , [8] , [9] ]. In one study, the rate of SARS-CoV-2 mutation was estimated to be 4.133 x 10 -4 substitutions/site/year [ 8 ], which is similar to the mutation rate of other coronaviruses [ 10 ].…”
mentioning
confidence: 99%
“…Emerging data report world-wide evolutionary changes of the SARS-CoV-2 virus [ [7] , [8] , [9] ]. In one study, the rate of SARS-CoV-2 mutation was estimated to be 4.133 x 10 -4 substitutions/site/year [ 8 ], which is similar to the mutation rate of other coronaviruses [ 10 ]. Interestingly, the majority of documented SARS-CoV-2 mutations involve G-U and C-U substitutions with nearly 50% of all mutations involving C-U substitutions [ 10 , 11 ].…”
mentioning
confidence: 99%